Pencarian Dasar-dasar Filosofis bagi Keberadaan Filsafat Nusantara - Kartika, Ganang Dwi (Wacana, Journal of the Humanities of Indonesia, 2004)
The meaning of philosophy in Indonesian has become an interesting topics, especially when it is related to another concept, culture. Some Indonesian dictionary writers defined "filsafat" (philosophy) in many ways from different aspects. However, the definitions have not reflected the meaning accuracy, both from the linguistic pattern aspect and from its terminology. Besides that, the definitions, which come from Western, invite another question. If there is Western philosophy, then what about Eastern philosophy, especially Nusantara philosophy? That question is also discussed in this writing.